2015
DOI: 10.1007/s40279-015-0350-7
|View full text |Cite|
|
Sign up to set email alerts
|

Current Methodologies and Implications of Phase Identification of the Vertical Jump: A Systematic Review and Meta-analysis

Abstract: The results demonstrate that three common methods exist for determination of the VJ phases from force platform data. Consequently, each produce different values for force-time variables when used on a neutral data pool. There is a clear need for a robust agreed method for VJ analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 66 publications
3
41
1
1
Order By: Relevance
“…Another factor that deserves further comments is the type of jumps assessed here. The CMJ and SJ are consistent with the current literature [14,16,17,26,27]. Another important aspect of the present study is that it appears as the first work using the application in a Paralympic sport, in which it is known that physical assessements are lacking and should be increased [28].…”
Section: Comparison With Prior Work Myjump2supporting
confidence: 90%
“…Another factor that deserves further comments is the type of jumps assessed here. The CMJ and SJ are consistent with the current literature [14,16,17,26,27]. Another important aspect of the present study is that it appears as the first work using the application in a Paralympic sport, in which it is known that physical assessements are lacking and should be increased [28].…”
Section: Comparison With Prior Work Myjump2supporting
confidence: 90%
“…A recent systematic review highlighted a number of different methodologies used to determine the start time of the CMJ (Eagles, Sayers, Bousson, & Lovell, 2015). Three main studies were identified.…”
Section: The Identification Of the Start Of The Jump/ Integrationmentioning
confidence: 99%
“…The first method classifies the initiation of the jump as a 5% reduction in the vertical component of the ground reaction force (VGRF). This method was cited 96 times in the literature by a number of different authors (Eagles et al, 2015). The second and third method defines the start of the jump as the point when the VGRF exceeds a quiet standing value for the participant (typically a value 10 N).…”
Section: The Identification Of the Start Of The Jump/ Integrationmentioning
confidence: 99%
See 2 more Smart Citations